Effects of Xanthine Oxidase Inhibition in Hyperuricemic Heart Failure Patients. Issue 20 (19th May 2015) - Givertz, Michael M.; Anstrom, Kevin J.; Redfield, Margaret M.; Deswal, Anita; Haddad, Haissam; Butler, Javed; Tang, W.H. Wilson; Dunlap, Mark E.; LeWinter, Martin M.; Mann, Douglas L.; Felker, G. Michael; O'Connor, Christopher M.; et al.
<x xml:space="preserve">Abstract</x> Background— Oxidative stress may contribute to heart failure (HF) progression. Inhibiting xanthine oxidase in hyperuricemic HF patients may improve outcomes. Methods and Results— We randomly assigned 253 patients with symptomatic HF, left ventricular ejection fraction ⩽40%, and serum uric acid levels ≥9.5 mg/dL to receive allopurinol (target dose, 600 mg daily) or placebo in a double-blind, multicenter trial. The primary composite end point at 24 weeks was based on survival, worsening HF, and patient global assessment. Secondary end points included change in quality of life, submaximal exercise capacity, and left ventricular ejection fraction. Uric acid levels were significantly reduced with allopurinol in comparison with placebo (treatment difference, –4.2 [–4.9, –3.5] mg/dL and –3.5 [–4.2, –2.7] mg/dL at 12 and 24 weeks, respectively, both P<0.0001). At 24 weeks, there was no significant difference in clinical status between the allopurinol- and placebo-treated patients (worsened 45% versus 46%, unchanged 42% versus 34%, improved 13% versus 19%, respectively; P=0.68). At 12 and 24 weeks, there was no significant difference in change in Kansas City Cardiomyopathy Questionnaire scores or 6-minute walk distances between the 2 groups. At 24 weeks, left ventricular ejection fraction did not change in either group or between groups. Rash occurred more frequently with allopurinol (10% versus 2%, P=0.01), but there was no difference in serious adverse event rates between the groups (20% versus 15%, P=0.36). Conclusions— In high-risk HF patients with reduced ejection fraction and elevated uric acid levels, xanthine oxidase inhibition with allopurinol failed to improve clinical status, exercise capacity, quality of life, or left ventricular ejection fraction at 24 weeks. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00987415.